ANALISIS EFEKTIVITAS KEBIJAKAN DAN PROGRAM BADAN PENGENDALIAN DAMPAK LINGKUNGAN DAERAH (BAPEDALDA) KOTA BATAM TERHADAP PENINGKATAN PERSENTASE PELAKSANAAN AMDAL - dompak, timbul; riyanda, riko (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2018)
Prototype of Batam as an industrial city in Indonesia with a variety of large factories has impacts on the environment. For example, waste and air pollution. AMDAL (Environmental Impact Assessment) issue becomes an urgent issue for Batam government which involves the role of Bapedalda Batam. The data of Batam Bapedalda from 2011 to 2015 showed the improvement of AMDAL. This study aims atanalyzing the policies and programs of Batam Environmental Impact Management Agency (Bapedalda) to the increase of AMDAL percentage. Method of collecting datawas done by interview, observation and documentation. Technique of selecting informant was purposive sampling, data analysis technique was done by data reduction, data presentation and conclusion. For large-scale industrial areas such as Batamindo, Kabil, Panbil the implementation of AMDAL have been effective but for the coastal area is still less effective because of investor low awareness. There are three things to increasethe percentage of AMDAL: (1) increasing the investor requirement of voluntary from company, (2) effort in socialization context, door to door service, (3) public awarenessby applying law enforcement.